FAKTOR YANG MEMPENGARUHI KEPUTUSAN BERINVESTASI PADA MASA PANDEMI COVID-19 (Studi Kasus : Masyarakat Desa Mayang, Gatak Sukoharjo) - Sari, Novita Diana; Pamikatsih, Tri Ratna (Jurnal Ilmu Manajemen, 2022)
This study aims to determine whether there is an influence between financial literacy, financial behavior, and income on investment decisions of rural communities during the Covid-19 pandemic. This type of research is quantitative research with data obtained from distributing questionnaires to 110 village residents. The data analysis used included descriptive analysis and multiple linear regression analysis with the help of the SPSS version 25 program. This study concludes that financial literacy has a positive and significant effect on investment decisions. Unlike the case with financial behavior which has a negative and significant influence on investment decisions. Similar to financial literacy, income also has a positive and significant influence on investment decisions. People should improve their investment decisions because they can be used for savings in preparing for future needs. This can be done by setting aside a portion of the income received, studying and understanding various kinds of financial information and how to manage finances.